2017
DOI: 10.4236/gep.2017.53014
|View full text |Cite
|
Sign up to set email alerts
|

Soil Macrofauna Behaviour in the Presence of Pesticides and Organic Amendments

Abstract: Insects attack vegetable crop, leading to an overuse of pesticides. Organic amendments are recommended to increase soil fertility. The impact of two insecticides, on soil macrofauna under rainfed cultivation of tomato (Lycopersicon esculentum L.) with or without organic amendments was evaluated.The insecticides were Lambda Super (lambda-cyhalothrin) and Dursban (chlorpyrifos ethyl) and organic amendments were compost, pig manure and cattle manure. An experimental device in split-plot with three replicate was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
3
0
5
Order By: Relevance
“…In this study, the authors reported a greater effect of pesticides on soil macrofauna members (worms, termites, beetles, ants, bedbugs, spiders, and spiders). In addition, Nare et al [21] showed in the treatments of organic fertilization, such as (bovine manure, swine manure and a compound of vegetal residues + bovine manure) there was a increase in the abundance of earthworms and termites, even in the presence of pesticides…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the authors reported a greater effect of pesticides on soil macrofauna members (worms, termites, beetles, ants, bedbugs, spiders, and spiders). In addition, Nare et al [21] showed in the treatments of organic fertilization, such as (bovine manure, swine manure and a compound of vegetal residues + bovine manure) there was a increase in the abundance of earthworms and termites, even in the presence of pesticides…”
Section: Resultsmentioning
confidence: 99%
“…; Article no.JEAI.41008 increase in the abundance of certain species [21] observed a cyhalothrin and chlorpyrifos insecticides used to control tomato pests on soil fauna. In this study, the authors reported a greater effect of pesticides on soil a members (worms, termites, beetles, ants, bedbugs, spiders, and spiders).…”
Section: Resultsmentioning
confidence: 99%
“…Ce qui montre que les pesticides étudiés ont été toxiques pour la macrofaune du sol entraînant ainsi une baisse de sa densité. Nos résultats corroborent ceux de plusieurs auteurs dont Robertson et al (1998), Charbonnier et al (2015 et Naré et al (2017). Ces derniers auteurs, dans une étude similaire, ont montré que la Lambdacyhalothrine entraînait une élimination totale de la population de termites même en présence du compost.…”
Section: Période De Prélèvement Du Solunclassified
“…Par ailleurs, le compost favorise également le développement de la macrofaune du sol dû aux nutriments divers qu'il renferme (Charland et al, 2001). Nos résultats concernant l'impact des pesticides testés sur la diversité de la macrofaune corroborent ceux de Traoré et al (2012) et Naré et al (2017) qui ont obtenu un meilleur indice de diversité et d'équitabilité de la macrofaune du sol en présence du compost. Ainsi, le compost améliore la diversité de la population de macrofaune, toute chose qui est en faveur d'une fertilisation des sols par application du compost.…”
Section: Période De Prélèvement Du Solunclassified
“…In Burkina Faso studies have shown the use of several pesticide formulations at widely varying doses (Gomgnimbou et al 2009). Although effective in controlling crop pests, pesticide use causes damage that leads to reduced soil fertility (Schreinemachers & Tipraqsa 2012;Naré et al 2017). After pesticide application, a significant portion is concentrated in the soil as a result of runoff, infiltration, adsorption and desorption processes.…”
Section: Introductionmentioning
confidence: 99%